Cast versus functional brace in the rehabilitation of patients treated non-operatively for a rupture of the Achilles tendon: protocol for the UK study of tendo achilles rehabilitation (UK STAR) multi-centre randomised trial. Issue 10 (24th October 2017) - Achten, Juul; Parsons, Nick R; Kearney, Rebecca L; Maia Schlüssel, Michael; Liew, Anna S; Dutton, Susan; Petrou, Stavros; Ollivere, Benjamin; Lamb, Sarah E; Costa, Matthew L
Abstract : Introduction: Achilles tendon rupture affects over 11 000 people yearly in the UK, and the incidence is increasing. Controversy remains with regard to the best rehabilitation strategy for these patients. In operatively treated patients, functional bracing provides better outcomes compared with plaster casts. However, the role of functional bracing in non-operatively managed patients is unclear. This is the protocol for a multicentre randomised trial of plaster cast immobilisation versus functional bracing for patients with a non-operatively managed Achilles tendon rupture. Methods and analysis: All adults presenting with a primary rupture of the Achilles tendon will be screened. Non-operatively treated patients will be eligible to take part in the trial. Broad eligibility criteria will ensure that the results of the study can be generalised to the wider patient population. Randomisation will be on a 1:1 basis. Both rehabilitation strategies are widely used within the National Health Service. Standardised protocols will be followed, and details of plaster material and brace will be as per the site's usual practice. A minimum of 330 patients will be randomised to obtain 90% power to detect a difference of 8 points in Achilles Tendon Total Rupture Score at 9 months. Quality of life and resource use will be collected at 3, 6 and 9 months. The differences between treatment groups will be assessed on an intention-to-treat basis. The results of the trial-based economic evaluation will be expressed in terms of incremental cost per quality-adjusted life-year gained. Ethics and dissemination: The National Research Ethic Committee approved this study on 18 March 2016 (16/SC/0109). The National Institute for Health Research Health Technology Assessment monograph and a manuscript to a peer-reviewed journal will be submitted on completion of the trial (summer 2019). The results of this trial will substantially inform clinical practice on the clinical and cost-effectiveness of the treatment of this injury. This study has been registered on the International Standard Randomised Controlled Trial Number registry with reference no ISRCTN62639639 .